ChemInform Abstract: Topologically Identical, but Geometrically Isomeric Layers in Hydrous α‐, β‐Rb[UO2(AsO3OH)(AsO2 (OH)2)]·H2O and Anhydrous Rb[UO2(AsO3OH)(AsO2(OH)2)]. Issue 31 (5th August 2014) - Yu, Na; Klepov, Vladislav V.; Villa, Eric M.; Bosbach, Dirk; Suleimanov, Evgeny V.; Depmeier, Wulf; Albrecht‐Schmitt, Thomas E.; Alekseev, Evgeny V.
Abstract Yellow‐green block‐shaped crystals of RbUO2(AsO3OH)(AsO2(OH)2) (I) and green block‐shaped crystals of β‐Rb[UO2(AsO3OH)(AsO2 (OH)2)]·H2O (II) are simultaneously hydrothermally synthesized from an aqueous mixture of UO2(NO3)2, RbNO3, and As2O3 in the molar ratio of 1:9:10 (autoclave, 150 °C, 48 h).